Development of stereoselective routes to natural product inspired compound collections via Lewis acid and -base catalysis - Danda, Adithi (Technische Universität Dortmund, 2015)
Natural product inspired compound collections embody structural scaffolds derived from biologically relevant and prevalidated fractions of chemical structure space explored by nature. These structural scaffolds are also referred to as privileged given the fact that the number of structural motifs of protein and natural products is limited. The probability that compound libraries inspired by natural products, will be biologically relevant is high and is also a viable guiding principle for the identification of small molecules for chemical biology and medicinal chemistry research. The present work addresses the synthesis of compound libraries inspired by natural product scaffolds. The thesis is divided into two main parts; the first part describes the synthesis of the indoloquinolizine scaffold and related analogs like the harmicine scaffold via a two-step reaction sequence, which involves a Pictet-Spengler cyclization step followed by a Au(I) catalyzed intramolecular hydroamination reaction, yielding the desired indole derived scaffolds. In the second part a synthetic methodology involving an asymmetric [4+2] annulation between electron deficient cyano chromones and α-allene esters was developed, which offered an easy stereoselective access to the optically active tetrahydroxanthone scaffold.
Entwicklung stereoselektiver Synthesen von naturstoffinspirierten Substanzbibliotheken durch Lewissäure und –basenkatalyse
Keywords: Gold catalysis; Pictet-Spengler reaction; Indoloquinolizine; Phosphine catalysis; Tetrahydroxanthone scaffold; Amino acid derived phosphine; 570